An assessment of the relationship between public debt, government expenditure and revenue in Namibia (Public Sector Economics - submission site, 2020)
This paper investigates the relationship between government expenditure, government revenue and public debt in Namibia by employing the data of these variables for the period 1980 to 2018. An error correction model (ECM) was employed to analyse the short-run dynamics and a positive relationship between government expenditure and government revenue was found. Similarly, there is supporting evidence that an increase in public debt will stimulate government expenditure. The error correction term indicates that any disequilibrium is corrected at an annual speed of 46.4 percent. Additionally, the pair-wise Granger causality test fails to support the spend-revenue hypothesis. However, there is supporting evidence that the tax-spend hypothesis does hold for Namibia. The study recommends that policy-makers should thoroughly review government expenditure and bring it to optimal levels in order to prevent the widening of public debt.